EFEKTIVITAS KEBIJAKAN PENGGUNAAN APLIKASI SISTEM INFORMASI KELUARGA (New SIGA) DALAM PELAPORAN HASIL KEGIATAN DI UPTD PENGENDALIAN PENDUDUK WILAYAH CICURUG KECAMATAN CICURUG KABUPATEN SUKABUMI - Muhammad Sulaeman Nur, Muhammad Sulaeman Nur; Virgian Septia Lesmana (Jurnal Dialektika Politik, 2024)
The research background, the Family Information System Application (New SIGA) is a set of structures that includes data, information, indicators, procedures, tools, technology and human resources that are interrelated and managed in an integrated manner to direct actions or decisions that are useful in supporting family development. . The use of the Family Information System Application (New SIGA) in reporting activity results aims to provide convenience for data and information managers at all regional levels in terms of managing annual and monthly report data. This study aims to determine the effectiveness of using the Family Information System Application (New SIGA) in reporting the results of activities at the UPTD Population Control in the Cicurug Region, Cicurug District, Sukabumi Regency. The method used in this study is a descriptive method with a qualitative approach, where this study intends to describe and interpret a natural condition. The results obtained include, among others, the effectiveness of the use of Family Information System Applications (New SIGA) in reporting the results of activities that will be achieved by applying 3 effectiveness concepts including Optimizing Objectives, System Perspectives and Human Behavior in Organizations. Based on the research results obtained, among others, the optimization of goals, system perspectives and human behavior in organizations in the process of using Family Information Systems (New SIGA) in Reporting Activity Results in UPTD Population Control in the Cicurug Region, Cicurug District, Sukabumi Regency has resulted in Effective Use of Information System Applications. Families (New SIGA) in Reporting Activity Results at UPTD Population Control in the Cicurug Region, Cicurug District, Sukabumi Regency has not been achieved optimally.